Successful project management practices - Rad, Parviz F.; Anantatmula, Vittal S. (Bingley, UK : Emerald, 2010)
If an organization has reached a high level of project management maturity, the organization should regard that as a reason for extreme pride among competitors. This book describes the attributes, procedures, and policies that reflect sophisticated organizations
bibliographical references and index
BSBA
Keywords: Project management